A JURISDIÇÃO CONSTITUCIONAL NA REPERCUSSÃO GERAL: ANÁLISE DOS TEMAS ADMITIDOS PELO SUPREMO TRIBUNAL FEDERAL E O CONFRONTO COM A TEORIA IDEALISTA DE LEGITIMAÇÃO DA REVISÃO JUDICIAL - Guzansky, Clivia Marcolongo Pereira (2022)
Constitutional jurisdiction in “Repercussão Geral”: analysis of the themes admitted by the Brazilian Supreme Court and the confrontation with the idealist theory of legitimation of judicial review The present study analyzed the thematic agenda of the Brazilian Supreme Court within the procedural technic named “repercussão geral”, used by the Court as a tool for choosing constitutional themes within its jurisdiction. The problem that moved this investigation has to do with the suspicion of illegitimacy within the control of constitutionality of normative acts of the elected Powers by a Court that is not subjected to electoral accountability, which is accentuated by the suspicion that the theories that support the exercise of this power by a judicial body would not be reflected in the reality of the Court. The lack of adherence to the theoretical foundations that justify the use of this power was the object of studies that determined whether the Brazilian Supreme Court’s thematic agenda in the context of centralized judicial review would preferentially be ordered for the defense of fundamental rights, or for the exercise of other roles unrelated to the legitimating discourse. The present work sought to extend this investigation, examining the appeals admitted by the Brazilian Supreme Court as paradigm of issues of “repercussão geral”. Following a research methodology based on the technique of content analysis with attention to contingencies, this study presents its own classification to show an overview of the thematic preferences of the Court, covering with empirical data an area of the constitutional jurisdiction of the Judiciary Power not sheltered by previous studies, with the hope of assisting the legal community in understanding the functions performed by the Brazilian Supreme Court and the position that it occupies in the national democratic arrangement, also aiming to provide statistical data that can contribute to the development of a morally sober approach of the constitutional dogmatic, which seeks to influence and transform reality from itself.